Actin as a potential target for decavanadate - Ramos, Susana (2012)
ATP prevents G-actin cysteine oxidation and vanadyl formation specifically induced by decavanadate, suggesting that the oxometalate–protein interaction is affected by the nucleotide. The ATP exchange rate is increased by 2-fold due to the presence of decavanadate when compared with control actin (3.1×10−3 s−1), and an apparent dissociation constant (kdapp) of 227.4±25.7 μM and 112.3±8.7 μM was obtained in absence or presence of 20 μM V10, respectively. Moreover, concentrations as low as 50 μM of decameric vanadate species (V10) increases the relative G-actin intrinsic fluorescence intensity by approximately 80% whereas for a 10-fold concentration of monomeric vanadate (V1) no effects were observed. Upon decavanadate titration, it was observed a linear increase in G-actin hydrophobic surface (2.6-fold), while no changes were detected for V1 (0–200 μM). Taken together, three major ideas arise: i) ATP prevents decavanadate-induced G-actin cysteine oxidation and vanadate reduction; ii) decavanadate promotes actin conformational changes resulting on its inactivation, iii) decavanadate has an effect on actin ATP binding site. Once it is demonstrated that actin is a new potential target for decavanadate, being the ATP binding site a suitable site for decavanadate binding, it is proposed that some of the biological effects of vanadate can be, at least in part, explained by decavanadate interactions with actin.